Murdoch mysteries. Season 15 [videorecording (DVD)] - Bisson, Yannick, 1969-; Joy, Hélène; Craig, Tom, 1962-; Harris, Jonny; Jennings, Maureen (Acorn Media, 2022)
Detective Murdoch seeks to find and protect his newly discovered son from the Black Hand gang. Meanwhile, Brackenreid's son has sprung loose from jail and is on the run, and Crabtree finds himself in a compromised situation as he tries to save Effie from her kidnappers.